Blood Pressure Values in School Age Children in Medan - T. M. Thaib; Hisworo Multi Alam; Agusnadi Munar Lubis; Rafita Ramayati; Rusdidjas Rusdidjas (Indonesian Pediatric Society Publishing House, 2018)
A cross sectional study on blood pressure in school children aged 6 to 16 years was carried out in the city of Medan from November 1 through January 31, 1993. By using stratified random sampling, 660 school children (336 boys and 324 girls) were enrolled. Blood pressure was measured using standard sphygmomanometer as recommended by The Second International Symposium on Hypertension in Children (1985). Relationships between the mean values of systolic and diastolic pressures with age and sex were sought for. There was a tendency that both systolic and diastolic blood pressures increased with increasing age. Based on percentile's graphic for age and sex, blood pressure higher than 95th percentile was found in 15 boys (4.5%) and 15 girls (4.6%) and 70% of them were in 11-16 years age group. Statistically significant correlations were found (p<0.001) between blood pressures and height as well as weight; however the correlation coefficients were only weak to moderate.